Ns Asuhan Keperawatan Pada Ny. I Dan Ny. R Dengan Cerbrovascular Disease (CVD) Di Ruang Inap Penyakit Dalam Rumah Sakit Umum Daerah Kota Tangerang Selatan - Muhamad Ridlo (Indonesian Journal of Nursing Scientific, 2023)
Background: Stroke or Cerebrovascular Disease (CVD) is a non-communicable disease which is one of the main causes of disability and could lead to death after heart disease and cancer in various developed and developing countries. Objective: To obtain an overview and be able to perform nursing care in patients with CVD. Methods: An analytical descriptive research design with a case study approach. The sample in this case study consists of Mrs. I and Mrs. R with a CVD diagnosis guided by medical surgical nursing care. Results: After doing nursing care for 3x24 hours on Ny. I, the results was that the risk of ineffective cerebral perfusion was partially resolved because there was no increase in consciousness, acute pain was partially resolved because the pain scale decreased to a scale of 4 (moderate), verbal communication disorders were partially resolved because dysarthria and speech disorders did not decrease. While on Mrs. R after nursing care for 3x24 hours, the results was that the risk of ineffective cerebral perfusion was not resolved because there was no increase in awareness, the nutritional deficit was not resolved because the portion of food decreased and impaired physical mobility was not resolved because there was no increase in muscle strength. Conclusion: The it can be concluded that speech therapy is an effective way stroke patients with speech muscle weakness while Range Of Motion (ROM) therapy is less effective in patients with extremity muscle weakness with recurrent stroke events. It is recommended that nurses are able to carry out nursing interventions, especially ROM therapy and health education effectively to increase muscle and joint strength.